Long-term evaluation of physical activity habits after epilepsy surgery - Leite,Adriana (2009)
OBJETIVES: Studies have shown that people with epilepsy have a low degree of participation in physical activities. The purpose of this study was to assess the physical exercise habits in patients after epilepsy surgery using a standardized questionnaire. MMETHODOLOGY: The study population consisted of 102 patients submitted to cortico-amigdalo-hippocampectomy. A questionnaire was designed to assess physical activities participation before and after surgery. Patients were classified as physically active, inadequately active or sedentary. The questionnaire was applied pre-operatively and after a mean of 47 months post-operatively. RESULTS: Forty eight per cent of the patients participated in physical activities before surgery and 56% of them did so post-operatively. No considerable changes in physical activity participation were observed after surgery. Additionally, the frequency they needed supervision during exercise, were advised by a physician not to practice exercise or cautioned by a relative or friend against participation in sports did not change significantly after successful epilepsy surgery. Less exercise-related seizures occurred postoperatively. CONCLUSION: Difficulties adapting to seizure freedom and psychosocial and psychiatric co-morbidity might be important factors interfering in these physical activity habits. A multidisciplinary approach might be the only way to try to alter some aspects of these patients' postoperative life style.